The Brainstem Auditory Evoked Potential: A Reinterpretation of its Electrogenesis - A Shaw Nigel (Journal of Otolaryngology Advances, 2025)
Depending upon the species, the brainstem auditory evoked potential (BAEP) consists of four or five major high frequency components. According to longstanding doctrine, each wave represents the sequential activation of successively higher nuclei and tracts from the 8th (auditory) nerve to the midbrain (inferior colliculus). Although this conceptual framework has acquired the status of near dogma, surprisingly little evidence exists in support. In the present analysis, a new interpretation of the electrogenesis of the BAEP is proposed which is simpler although it retains skeletal elements of the older explanation. The revised model is mostly derived from two distinct sources. In the first, the timing of the BAEP waves is compared with that of cortical activity for a range of mammals including humans, monkeys, cats, rats and guinea pigs. It is demonstrated that for each of these, the conduction time of the acoustic signal to the cortex from the putative midbrain component (wave IV or V) is so unrealistically long that it implies that the entire waveform must arise in the peripheral pathways of the auditory system. In the second, a retrospective analysis is made of click repetition rates on the BAEP using extradural electrodes. It was shown that at high rates of stimulation (about 100/sec), the behavior of the waveform is almost totally at variance with the expectations of the conventional model. The essence of the revised conception is that all BAEP waves are just variations of the compound action potential of the 8th nerve, albeit generated or regenerated via separate routes and different methods. Such an explanation would thereby account for their near uniform sharp morphology as well as creating the impression of a composite neuronal response. More specifically, in the case of a four component BAEP, wave I is assumed to be generated by the normal air conduction route in an identical manner to the conventional explanation. In contrast, wave ll is assumed to be generated via bone conduction in the temporal skull thereby bypassing the transduction process in the middle ear. Wave lll is assumed to be generated by the first echo of the bone-conducted sound wave. Likewise, the second rebound within the temporal bone serves as the stimulation to evoke wave lV. As the energy of the auditory stimulus gradually dissipates, it may still continue to generate a train of lower amplitude potentials. It is concluded that the BAEP may contain little or no brainstem or midbrain activity and therefore the term BAEP may be a misnomer. A more appropriate epithet might therefore be the auditory nerve evoked potential or ANEP.
Keywords: Air conduction